MODEL PEMBELAJARAN DPA (LITERACY, ARGUMENTATION, NEW CONCEPT AND PROJECT) UNTUK MENINGKATKAN KETERAMPILAN ABAD 21: MODEL PEMBELAJARAN DPA (LITERACY, ARGUMENTATION, NEW CONCEPT AND PROJECT) UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 - Dewi Permata Ayu; Amelia Putri; Muhiddin Palennari (STKIP Subang, 2026)
ABSTRACTThis research aims to develop the DPA learning model to enhance the quality of biology education at the senior secondary school level (SMA/equivalent). This model is an extension of Project-Based Learning (PjBL), designed to overcome challenges such as the low literacy of students. The background of this study is rooted in the identified gaps: low scientific literacy, lack of critical thinking and scientific argumentation skills, and minimal in-depth conceptual understanding, which makes the learning process less meaningful for students. The DPA model was developed as an innovation of Project-Based Learning (PjBL) with specific integrations to address these skill deficiencies while simultaneously internalizing the value of meaningful learning. Furthermore, this model is also expected to foster meaningful learning values within the educational process.The method employed is a qualitative literature review. The researchers conducted an in-depth and systematic analysis of various key literature relevant to PjBL and the 21st-century skills framework. The theoretical synthesis from this analysis was then utilized to formulate and structure the DPA Model framework, which consists of seven structured learning stages. The development of the DPA model was carried out by synthesizing these theories into seven learning stages. The results of the analysis and development indicate that the DPA Model comprises seven systematic main stages. These stages include: Literacy and problem orientation; Initial argumentation and project planning; Exploration of new concepts and argument development; Project implementation; Final argumentation and project presentation; Reflection and concept confirmation; and Implementation of conceptual knowledge in daily life and the surrounding environment. This DPA model offers a solution for improving learning quality, focusing on authentic, collaborative, and reflective experiences. The development of this model is expected to effectively enhance students' literacy, argumentation skills, and concept mastery, making them competent in line with 21st-century competencies and skills.